World Wonders: Gaza Sarcophagi (The Biblical archaeology review, 2024)
These anthropoid sarcophagi reflect the convergence of Egyptian and Canaanite burial practices. They originate from the cemetery of Deir el-Balah, located 8 miles south of Gaza City. Dating from the 14th and 13th centuries BCE, the coffins were crafted by building up coils of clay that were then shaped. The lids would be cut out […]